Evolution as a religion : strange hopes and stranger fears - Midgley, Mary, 1919- (Routledge, 2002)
This work exposes the illogical logic of poor doctrines that shelter themselves behind the prestige of science. Midgley examines how science comes to be used as a substitute for religion and points out how badly that role distorts it.